Factors affecting the study location preferences of Bachelor of Library and Information Science students of the University of the Philippines Diliman - Geroca, Jeseliza A.; Buenrostro, Iyra S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2013)
This study was conducted to determine the study location preferences of undergraduate students of the School of Library and Information Studies (SLIS) in the University of the Philippines (UP) Diliman and the factors that affect these preferences. Several factors were classified into five different categories: demographic, environmental, sociological, physiological and technological.
The study employed a survey questionnaire to gather relevant data from Bachelor of Library and information Science (BLIS) students of UP Diliman during the first semester of academic year 2012-2013. A total of one-hundred fifteen (115) UP Diliman BLIS students responded to the survey. Frequency counts, percentages and rankings were used to analyze and present the results of quantitative data gathered. Collected qualitative data was explained and presented in narrative form.
According to the results of the survey, BLIS students have basic requirements for an ideal study location. BLIS students prefer a study location that is well-lit and well-ventilated with the right temperature. The place should have educational materials available including electronic journals. It should also have available Internet connection that allows access to all types of websites. The students' preferred study location should also allow them to use their own electronic devices and charge them as well. Finally, photocopy services should be available or easily accessible.
Survey results also revealed the factors that affect the study location preferences of UP Diliman BLIS students. Age, year level, employment status and chosen LIS track were the demographic factors found to affect BLIS students' location preferences. The environmental factors found to greatly affect their study location preferences were lighting, availability of educational materials, ventilation, and temperature. Several technological factors turned out to be highly important to the respondents as well and therefore greatly affect their study location preferences. These technological factors were the availability of an Internet connection, provision for use of own electronic devices, access to all types of websites, access to electronic journals, provision for charging of electronic devices and availability of photocopy services.
Furthermore, the study was conducted to examine how well the UP SLIS Library meets the study location preferences of UP Diliman BLIS students and how it can be improved to satisfy the students' preferences. According to the respondents, the UP SLIS Library's provision for individual studying, availability of education materials, lighting, access to electronic materials, lighting, access to electronic journals, temperature, accessibility or proximity, ventilation, availability of study support personnel, space to spread out materials, and provision for studying with another person were excellent. On the other hand, the respondents suggested the use of chairs that are softer, lighter, and easier to move in the UP SLIS Library. They also suggested placing a snack facility and a photocopy service nearby. They mentioned putting up separate rooms for group study sessions and repairing or upgrading computers and printers as well. Finally, UP Diliman BLIS students proposed that the UP SLIS Library improve its Internet connection speed, allow access to all types of websites, and provide free charging services for electronic devices used for studying.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) School of Library and Information Studies -- Students; Study environment